The Use of Language in Criminal Procedures Code (CPC) and The Nigeria Police Act and Regulations: A Critical Perspective - Oyedokun Alli, Wasiu Ademola (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
This paper examines issues that pertain to the use oflanguage in law, with particular reference to the wordings of the Criminal Procedures Code (CPC) and the Police Act and Regulations. The major thrust of the study is that since law directly affects the lives of all the citizens of a particular country, the interpretations of statutes, bills and acts should not generate uncertainties in scope, meaning and effects. The paper concludes that certain mechanisms should be put in place to minimize incidents of vagueness and indeterminacy of reference in the interpretations of such statutes and acts.